2011
DOI: 10.5665/sleep.1400
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Fragmentation of Rest-Activity Patterns in Elderly Individuals Using a State Transition Analysis

Abstract: Probabilistic analyses of the transition dynamics of rest-activity data provide a high-throughput, automated, quantitative, and noninvasive method of assessing the fragmentation of behavioral states suitable for large scale human and animal studies; these methods reveal age-associated changes in the fragmentation of rest-activity patterns akin to those described using polysomnographic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 51 publications
(108 reference statements)
3
98
0
Order By: Relevance
“…The plot is generally divided into 3 regions: a falling region where a rapid decline is observed, followed by a constant non-zero probability region, and ending with a rising region where a slow increase occurs at the end of the longest runs. Similar to Lim and colleagues, we found that the rising regions were identified based on a relatively small number of data points and may represent an artifact (Lim et al, 2011 "usually" if the sleep behaviour occurred five to seven times a week, "sometimes" for two to four times a week, and "rarely" for zero to one time a week. Specific items are scored in a reverse order in order to make a higher score indicative of more disturbed sleep.…”
Section: Scoring and Data Analysissupporting
confidence: 86%
See 3 more Smart Citations
“…The plot is generally divided into 3 regions: a falling region where a rapid decline is observed, followed by a constant non-zero probability region, and ending with a rising region where a slow increase occurs at the end of the longest runs. Similar to Lim and colleagues, we found that the rising regions were identified based on a relatively small number of data points and may represent an artifact (Lim et al, 2011 "usually" if the sleep behaviour occurred five to seven times a week, "sometimes" for two to four times a week, and "rarely" for zero to one time a week. Specific items are scored in a reverse order in order to make a higher score indicative of more disturbed sleep.…”
Section: Scoring and Data Analysissupporting
confidence: 86%
“…As older age tends to be associated with more fragmented runs of activity, children would be expected to show a reduced tendency towards fragmented runs of activity compared to older individuals (Lim et al, 2011). In contrast, mean kRA was higher in the control group and surgical group compared to the elderly, indicating that children have an increased tendency towards fragmented runs of rest.…”
Section: Transition Probabilities Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…[25][26][27] Briefly, k RA is the probability per 15-sec period of having an arousal, as indicated by movement (a nonzero activity count) after a sustained (≥ ~5 min) period of rest (i.e., sleep). A higher k RA indicates greater sleep fragmentation.…”
Section: Assessment Of Sleep Fragmentationmentioning
confidence: 99%